Genome-Wide Association Study Uncover the Genetic Architecture of Salt Tolerance-Related Traits in Common Wheat (Triticum aestivum L.) - Quan, Xiaoyan; Liu, Jindong; Zhang, Ning; Xie, Chunjuan; Li, Hongmei; Xia, Xianchun; He, Wenxing; Qin, Yuxiang (Frontiers in Genetics, 2021)
Soil salinity is a serious threat to wheat yield affecting sustainable agriculture. Although salt tolerance is important for plant establishment at seedling stage, its genetic architecture remains unclear. In the present study, we have evaluated eight salt-tolerance related traits at seedling stage and identified the loci for salt-tolerance by genome-wide association study (GWAS). This GWAS panel was comprised of 317 accessions and was genotyped with the wheat 90 K single nucleotide polymorphism (SNP) chip. Totally, 37 SNPs located at 16 unique loci were identified and each explained 6.3-18.6% of the phenotypic variations. Among these, six loci were overlapped with previously reported genes or QTLs, whereas the other 10 were novel. Besides, nine loci were detected for two or more traits, indicating that the salt-tolerance genetic architecture is complex. Furthermore, five candidate genes were identified for salt-tolerance related traits, including kinase family protein, E3 ubiquitin-protein ligase-like protein and transmembrane protein. SNPs identified in this study and the accessions with more favorable alleles could further enhance salt tolerance in wheat breeding. Our results are useful for uncovering the genetic mechanism of salt tolerance in wheat at seeding stage.